Traditional Mandailing Natal Muslim Women's Clothing: An Analysis of Local Wisdom and the Spirit of Religious Practice According to Islamic Law - Putra, Dedisyah; Khalidi, Muhadi; Ritonga, Raja (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2025)
AbstractClothing is a personal right and freedom that integrates social and cultural aspects. This issue demonstrates the complexity and sensitivity of the topic of dressing for Muslim women, which often involves the interaction between personal beliefs, religious law, human rights, and social norms. This research is a type of phenomenological study that will reveal the relationship between traditional clothing of Muslim women in Mandailing Natal and how Islam views it. Data was collected through observation and interviews. The data analysis results show that historically, women in Mandailing Natal have maintained traditional clothing both for customary ceremonies and daily wear. Adaptations and the influence of contemporary trends have also impacted the declining interest among young men and women in preserving their traditional clothing. When weighed against the Islamic legal perspective, which emphasizes modesty, gender appropriateness, simplicity, purity and cleanliness, non-tightness, and the absence of haram elements, the traditional attire of Muslim women in Mandailing Natal is appropriate and should be preserved and maintained.Keywords: Clothing, Muslim Women, Customs, Islamic Law